Advances in the conventional clinical treatment for hepatoblastoma and therapeutic innovation. Issue 3 (8th June 2021) - Chen, Zhixue; Dong, Rui
Abstract : Background: Hepatoblastoma (HB) is a rare malignancy usually occurring in children under 3 years old. With advancements in surgical techniques and molecular biology, new treatments have been developed. Data resources: The recent literatures on new treatments, molecular mechanisms and clinical trials for HB were searched and reviewed. Results: Surgical resection remains the main option for treatment of HB. Although complete resection is recommended, a resection with microscopical positive margins (R1) may have similar 5-year overall survival and 5-year event-free survival (EFS) rates after cisplatin chemotherapy and the control of metastasis, as only once described so far. Indocyanine green-guided surgery can help achieve precise resection. Additionally, associating liver partition and portal vein ligation for staged hepatectomy can rapidly increase future liver remnant volume compared with portal vein ligation or embolization. Cisplatin-containing chemotherapies slightly differ among the guidelines from the International Childhood Liver Tumors Strategy Group (SIOPEL), Children's Oncology Group (COG) and Chinese Anti-Cancer Association Pediatric Committee (CCCG), and the 3-year EFS rate of patients in SIOPEL and CCCG studies was recently shown to be higher than that in COG studies. Liver transplantation is an option for patients with unresectable HB, and successful cases of autologous liver transplantation have been reported. In addition, effective inhibitors of important targets, such as the mTOR (mammalian target of rapamycin) inhibitor rapamycin, β-catenin inhibitor celecoxib and EpCAM (epithelial cell adhesion molecule) inhibitor catumaxomab, have been demonstrated to reduce the activity of HB cells and to control metastasis in experimental research and clinical trials. Conclusion: These advances in surgical and medical treatment provide better outcomes for children with HB, and identifying novel targets may lead to the development of future targeted therapies and immunotherapies.